Electroreflectance spectroscopy and scanning electron microscopy study of microrelief silicon wafers with various surface pretreatments - Gorbach, T.Ya.; Holiney, R.Yu.; Matiyuk, I.M.; Matveeva, L.A.; Svechnikov, S.V.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
The effect of various pretreatments on the performance of microrelief (textured) Si wafers was studied by the techniques of low-field electroreflectance spectroscopy, scanning electron microscopy, and electron diffraction. Four types of preliminary treatments were employed to prepare microrelief surfaces by anisotropic chemical etching: (i) cutting, (ii) cutting and mechanical polishing with Al₂O₃, (iii) cutting and chemical polishing with HNO₃:HF, and (iv) the standard industrial technique. Using the critical point energy Eg at the central point in the Brillouin zone (GIV₂₅ – GC₁₅ transition) and the phenomenological parameter of broading G to characterize the performance of the Si surface, it was found that anisotropic chemical etching performed after cutting produced the surface performance comparable to that of industrially fabricated wafers, but at a lower cost. Методами спектроскопії низькопольового електровідбиття, растрової електронної мікроскопії та електронографії досліджено вплив попередніх обробок поверхні кремнію (різка; різка та механічна поліровка; різка та хімічна поліровка; стандартна фабрична обробка) на досконалість анізотропно травлених мікрорельєфних пластин. Як критерій досконалості аналізуються енергія критичної точки Eg в центрі зони Бріллюена (переходи GIV₂₅ – GC₁₅ ), феноменологічний параметр уширення Г, рухливість носіїв заряду, морфологічні особливості поверхні та кристалічна структура. Показана можливість використання попередньої обробки різкою для виготовлення достатньо досконалих анізотропно травлених мікрорельєфних пластин. При цьому очікується зменшення їх кошторису. Методами спекроскопии низкополевого электроотражения, растровой электронной микроскопии и электронографии исследовано влияние предварительных обработок поверхности кремния (резка; резка и механическая полировка; резка и химическая полировка; стандартная фабричная обработка) на совершенство анизотропно травленных микрорельефных пластин. В качестве критерия совершенства анализируются энергия критической точки Eg в центре зоны Бриллюэна (переходы GIV₂₅ – GC₁₅, феноменологический параметр уширения Г, подвижность носителей заряда, морфологические особенности поверхности и кристаллическая структура. Сделан вывод о возможности использования предварительной обработки резкой для получения достаточно совершенных анизотропно травленных микрорельефных кремниевых пластин. При этом ожидается снижение стоимости пластин.